The association of nutritional status and perceived on disease among Auxiliary Police in UiTM Selangor, Malaysia / Muhammad Syafiq Zainol - Zainol, Muhammad Syafiq (2016)
A cross-sectional study was done in Universiti Teknologi MARA (UiTM) Selangor campus in order to assess the degree of perceived on disease among auxiliary police. The campuses that included in this study are UiTM Shah Alam, UiTM Puncak Alam, UiTM Puncak Perdana and UiTM Sungai Buloh. Objective of the study was to determine the association of nutritional status and perceived on disease among auxiliary police aged 18 to 65 years old in UiTM Selangor. Auxiliary police (n=122) were recruited and answered questionnaire in a booklet (hardcopy) form. The questioQJ1aire consist of demographics criteria including age, gender, academic level and income. Another part of the questionnaire was used to measure the perceived on disease among respondents including their behavioural and cue to action. Nutritional assessment are done consisting of anthropometric assessment and dietary assessment. Height and weight were measured in order to calculate body mass index (BMI). Dietary assessment is done by two days 24 hours diet recall (24-HDR) via face to face interview and analysed using Nutritionist Pro Software. 42 out of 122 respondents are criterion has high level of perceived on disease (34.4%) and the remainder 80 persons have low level of perceived on disease (65.6%). Results show that there are association between academic levels and perceived on disease among respondents (p=0.042). However, there are no association between age, gender and income with perceived on disease. Majority of auxiliary police in UiTM Selangor are overweight (n=51). Result shows that there are significant association between BMI and level of perceived on disease among respondents (p <0.05). However, there are no significant correlation between perceived on disease and dietary intake. Perceived on disease had been identified significant to behavior of reading nutrient labelling, searching health information through internet, mass media and consultation with professional health care. The findings from this study showed that level of perceived on disease among auxiliary police in UiTM Selangor are low and if they continue being unconcern, it will lead them to get disease in future.